Exhausted Servers Deny Service - HTTP Get Attack - Alvin Prasad (Journal of ICT, Design, Engineering and Technological Science, 2019)
Hyper Text Transfer Protocol (HTTP) Get attack is the most common type of Denial of Service attacks (DOS) found today. It is common because it is very easy to implement/set up. It disallows the services of an organization to be offered to users by flooding the server with a legitimate request, thus exhausting the server. This prevents the server from providing services to legitimate users, which leads to organizations and businesses losing millions of dollars. Several mitigation techniques are available, but these techniques are still insufficient to detect and combat malicious requests. The objective of this review paper is to provide the readers with information on DoS attacks and the attackers’ intention behind these illegal activities. The critical analysis of the current literature provides insights on how to mitigate and prevent these types of attacks. This article suggests limiting the response time for each request from the server, and in dealing with the response, it can use the latest verification system. This research can help the organizations and the solution developers in mitigating and preventing the flooding attack thus, allowing organisations to flourish as information is readily available to the users.